1986
DOI: 10.1007/bf00026692
|View full text |Cite
|
Sign up to set email alerts
|

Effects of peatbog ditching in lakes: Problems in paleolimnological interpretation

Abstract: Recent sediment stratigraphy in two lakes with extensive artificial drainage of surrounding peatbogs was studied by 210 Pb and 137 Cs dating and chemical and diatom analyses . In contrast to many other lakes with similar ditching history, the visual appearance of the recent sediments in both of these lakes is homogeneous . In the larger lake, Kyyvesi, the sediment accumulation rate seems to have increased, but no major changes in the chemical properties or diatom stratigraphy are to be seen . In the organic dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…In fact, DI-TP declined markedly in Lake Iso Kivijärvi at this time, most likely because of the increase in T. fenestrata and the corresponding decline in A. ambigua. A similar pattern of changes in diatoms was reported from a peatland drainageaffected lake in Eastern Finland, with responses to early land use followed by more intensive changes in the 1970s (Liehu et al 1986).…”
Section: Intensive Forest Drainage In the 1960s And 1970ssupporting
confidence: 70%
“…In fact, DI-TP declined markedly in Lake Iso Kivijärvi at this time, most likely because of the increase in T. fenestrata and the corresponding decline in A. ambigua. A similar pattern of changes in diatoms was reported from a peatland drainageaffected lake in Eastern Finland, with responses to early land use followed by more intensive changes in the 1970s (Liehu et al 1986).…”
Section: Intensive Forest Drainage In the 1960s And 1970ssupporting
confidence: 70%
“…Comparisons of diatom assemblages and DI‐TP between the core bottom and present‐day samples from this site indicate much more important changes than those between c. 1850 and present‐day, because of increased abundances of Asterionella ralfsii (a taxon that was not recorded in pre‐ c. 1850 sediments). The ecology of this taxon is not well known but appears to be indicative of peatland disturbance and nutrient enrichment (Liehu, Sandman & Simola 1986). It could therefore be argued that c. 1850 is not an appropriate reference date for Keel, and this may also be the case for several other lakes in catchments that until the mid‐19th century supported far higher human population densities than today.…”
Section: Discussionmentioning
confidence: 99%
“…Such differences are reconcilable with known forest effects on atmospheric pollutant transfer to runoff water (Harriman & Morrison 1982;Unsworth 1984). However, unlike the RLGH, there is a major change in the diatoms at this site, beginning in the late-1970s and culminating in 1988 with a mass occurrence of , an acidophilous diatom indicative of peatland disturbance and nutrient enrichment (Liehu et al 1986). As acid deposition changes are similar to those at the RLGH it is suggested that the recent floristic changes at Loch Grannoch are an indirect result of forestry management.…”
Section: Discussionmentioning
confidence: 57%